Rice Harvest Failure Risk Analysis Using Extreme Value Theory Based on Weather Index for Agricultural Business Supply Chain Management - Riaman, Riaman; Sukono, Sukono; Supian, Sudradjat; Ismail, Noriszura (International Journal of Supply Chain Management, 2020)
This paper discusses the formulation of a risk model for paddy agricultural insurance in Indonesia. Indonesia as an agricultural country with a tropical climate, where the sun shines throughout its time, farmers can plant crops throughout the season. In particular, rice farming is currently an inseparable part of most agrarian societies in Indonesia, especially in West Java. However, changes in air temperature, weather and annual rainfall, which sometimes changes uncertainly, cause changes in cropping patterns. This weather uncertainty will certainly increase the risk of crop failure. This paper will analyze the effect of climate variables on the risk of crop failure. The climate variables in this analysis consist of temperature, wind speed, maximum temperature, minimum temperature, and rainfall. The method to be developed here is to use the parametric method which will be used as a reference to determine the magnitude of risk, namely generalized pareto distribution and peak over threshold as a threshold. The results obtained that the greatest risk of losses to farmers occurred in November, December, January, February and March with a value of 0.17485. The organization of this paper consists of introduction, methodology, results and discussion, and conclusions.